Casuistry and early modern Spanish literature - Bidwell-Steiner, Marlen; Scham, Michael, 1969- (Foro hispánico, 2022)
"Casuistry and Early Modern Spanish Literature examines a neglected yet crucial field: the importance of casuistic thought and discourse in development of literary genres in early modern Spain. Faced with the momentous changes wrought by discovery, empire, religious schism, expanding print culture, consolidation of legal codes and social transformation, writers sought innovation within existing forms (the novella, the byzantine romance, theatrical drama) and created novel genres (most notably, the picaresque). These essays show how casuistry, with its questioning of example and precept, and meticulous concern with conscience the particularities of circumstance, is instrumental in cultivating the subjectivity, rhetorical virtuosity and spirit of inquiry that we have come to associate with the modern novel"--